Re-analysing the concept of ecologically fragile lands (EFLs) with particular reference to Wayanad district, Kerala - Jiss K Varkey (Department of Forest Management and Utilisation, College of Forestry, 2012)
Concept mapping technique was employed to investigate how the stakeholders in Wayanad district conceived The Kerala Forest (Vesting and Management of Ecologically Fragile Lands) Act, 2003. Referencing a research framework informed by multiple views of the stakeholders, evaluation of 120 respondents was carried out by organizing into four equal groups. These groups consisted of (A) officials from forest, agriculture and revenue departments (B) ecologists, environmentalists and legal professionals (C) policy makers and local political leaders and (D) farmers and agricultural labourers in Wayanad. A set of 45 statements/ideas were generated by the respondents to describe their understanding on ecologically fragile lands (EFLs). Sensible sorting and individual statement rating were used to find out conceptual similarities and/or differences and to realize feasibility solutions. The outcome configured five clusters from the point map namely ecological dimensions, situational dimensions, socio-economic dimensions, framework dimensions and better EFL dimensions. The stress and fit measures and the bridging values substantiated the sensibility of multidimensional scaling (MDS) and subsequent clustering process. Cluster rating map confirmed highest average rating to ecological dimensions and lowest to the situational dimensions. Pattern matches and go-zones investigated divergence among stakeholders in terms of importance/feasibility rating. Large divergence was observed in two cases where importance rating done by farmers/agricultural labourers and feasibility rating offered by government officials or by the group consisting of environmentalists/legal professionals. Consensus was found with 28 statements/ideas when sourced out in the course of six possible junctures of go-zones. The output statements/re-oriented criteria and indicators envisaged EFLs as vital in sustaining ecological and climatic values of the landscape. Emphasis was made for adequate compensation to eligible farmers in ensuring fair justice in order to relieve the shared instabilities concerning implementation of the EFL Act, 2003. The findings laid down certain policy implications/recommendations on EFLs, useful in future course of actions.